Synthesis of metallic nanoparticles in deep eutectic solvents for electroanalytical applications - Gomes-Junior, Paulo Cardoso (2025)
In this work, the synthesis of metal nanoparticles (MNPs) in DES were developed for subsequent applications in electrochemical sensors based on two carbon materials: carbon black (CB) and multiwalled carbon nanotubes (MWCNT). First, a DES-based on choline chloride (ChCl) and urea (U) in a molar ratio of 1:2 (mol:mol ) was used as a stabilizing medium in the synthesis of ultrasmall nanoparticles (USNPs) (size < 1.0 nm) using a bottom-up approach based on solvothermal concepts, under mild temperature conditions (< 100 ºC). Platinum and cerium oxide USNPs with average sizes of 0.73 (± 0.07) nm and 0.204 (± 0.008) nm, respectively, were obtained using DES. SEM and TEM were used to morphologically characterize the USPtNPs and USCeOxNPs, revealing approximately spherical shapes with characteristic emission lines of platinum and cerium in the EDS spectrum. The ChCl:U-based DES was characterized by FT-IR and NMR spectroscopy, which indicated its formation through hydrogen bonds between the precursors. DSC studies demonstrated thermal glass transition and melting events for DES and its precursors. Furthermore, electrochemical sensors were developed: (i) for determination of riboflavin (RB) in commercial energy drinks and biological fluids using USPtNPs together with MWCNT; (ii) for determination of dopamine (DA) in biological fluids using USCeOxNPs with CB. In the voltammetric determination of RB, the USPtNPs-DES/MWCNT/GCE sensor achieved linear responses in the range of 0.02 – 1.2 µmol L−1, with a detection limit of 1.8 nmol L−1, and good repeatability and anti-interference characteristics. The USCeOxNPs-DES/CB/GCE sensor showed a linear response for DA in the range from 5.0 × 10−7 mol L−1 to 3.2 × 10−4 mol L−1, with a detection limit of 80 nmol L−1, good repeatability and anti-interference performances. Furthermore, both sensors were successfully applied to determine the target analytes in energy drinks and biological fluid samples. In this first part, both the synthesis of USNPs in DES and their applications in the sensors were successful. Subsequently, a new hydrophilic DES based on ChCl and diethanolamine (DEA) was developed, which included physicochemical, molecular and thermal characterizations. From the DSC analyses, a phase diagram was elaborated to determine the eutectic composition in the set of fractions, and the results showed that the eutectic point of the DES was in the molar ratio 1:3 (mol:mol) with a melting temperature of 285.8 K for ChCl:DEA. Additionally, characterizations performed by FT-IR and NMR allowed the identification of interactions between the DES precursors. The DES at the eutectic point was then used to synthesize AgNPs without adding a conventional reducing agent and under mild conditions (< 100 °C). The results of the morphological characterizations of AgNPs obtained by TEM, EDS, SAED, and XRD revealed varied shapes with emission lines characteristic of polycrystalline silver and crystallographic planes of face-centred cubic structures. Additionally, AgNPs were incorporated into a film based on MWCNT, dimethylformamide, and Nafion™. AgNPs-DES/MWCNT/GCE sensor showed a significant increase in the electrocatalytic activities related to the redox behavior of hydroquinone, good stability in the voltammetric responses, especially due to the AgNPs, that enabled a high value of apparent heterogeneous electron transfer rate constant (kapp) and low charge transfer resistance (Rct). The diffusion coefficient (Dapp) and catalytic constant (kcat) were estimated to be (4.1 ± 0.5) x 10−5 cm2 s−1 and 2.8 x 106 mol−1 L s−1, respectively. The results presented in this work show the importance of characterizing DES and that their applications in green syntheses can generate promising nanomaterials in electrochemical sensor applications.